Analisis Sistem Informasi Akademik Menggunakan Metode FAST Pada SDIT Al-Qudwah Pangkalpinang - sujono (NUANSA INFORMATIKA, 2023)
The Academic System is the management of academic data in an educational institution including at SDIT Al-Qudwah Pangkalpinang, which consists of managing student data, schedule data, attendance data, and grades data. However, management is currently still carried out manually without using technology. The downside is that the manual method is vulnerable to human error, the amount of time and effort needed to record and calculate so that data collection becomes less efficient and accurate, and it is prone to losing data values ​​that have been recorded. Therefore it is necessary to build a web-based information system that can manage academic data in a modern way so that time efficiency and data accuracy can be increased. To design, analyze and develop the system, the writers use the FAST method and UML tools. Using this web based academic information system can overcome the weaknesses faced by SDIT Al-Qudwah Pangkalpinang